Analisis Faktor-faktor Motivasional yang Berhubungan dengan Kinerja Bidan Desa dalam Pembinaan Kader Posyandu di Kabupaten Aceh Barat Tahun 2014 - Teungku Nih Farisni; Martha Irene Kartasurya; Atik Mawarni (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2016)
Indicator of posyandu work performance in West Aceh was still far below the target determined and there was a decrease during 2011-2012. The results of the preliminary study showed that the motivation of village midwives were still low in posyandu cadre coaching. The aim of this research was to identify the factors associated village midwives motivation in posyandu cadre coaching. The study was conducted quantitavely and qualitatively. The quantitative research used survey method with a cross sectional design. The subjects were 146 village midwives selected by clustered random sampling at public healthcare center level. Data colection was conducted by interviews using structured questionnaire. The bivariate analysis used Chi Square tests, and the multivariate analysis used logistic regression. The qualitative data was collected by in-depth interviews to the village midwives and analyzed by content analysis. The results showed that 64.4% of the respondents had low performance, 54.8% had less responsibility, 62.3% had insufficient potential development, 57.5% felt inadequate compensation, and 52.7% had less supervision. There were associations between responsibility (C= 0.237, p=0.006), potential development (C= 0.268, p=0.001), compensation (C=0.518, p=0.0001), working condition (C=0.237, p=0.006), supervision (C=0.261, p=0.002,) and the village midwife performance in posyandu cadres’s coaching. Compensation had the most significant effect on the village midwive motivation in posyandu cadres coaching (Exp-B=17.383, p=0.0001). The obstacles experienced by the village midwives in posyandu cadres coaching were insufficient fund, unavailable special training for the posyandu cadre coaching and unavailable health facilities. Compensation has the most significant effect on village midwive motivation in posyandu cadres coaching. It is suggested to public healthcare centers and Health office to implement refreshing cadre coaching and improving village midwives performance in by giving appreciation to village midwives who conducted posyandu cadre.